1996
DOI: 10.1073/pnas.93.14.7196
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental autoimmune encephalomyelitis by feeding myelin basic protein conjugated to cholera toxin B subunit.

Abstract: Oral administration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
122
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 32 publications
9
122
1
Order By: Relevance
“…administration of OVA/CTB conjugate effectively induces OVA-specific peripheral immunological tolerance, whether tested in normal BALB/c mice, OVA TCR Tg (DO11.10) mice, or in either BALB/c mice or Rag1 Ϫ/Ϫ mice transferred with OVA TCR Tg T cells. Consistent with our previous findings in other systems (17)(18)(19)(20)(21)(22), oral tolerance induction with Ag/CTB conjugate was superior to that induced with free Ag both in markedly increasing the efficacy of tolerization and in dramatically decreasing the effective amounts of Ag. The oral tolerance by i.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…administration of OVA/CTB conjugate effectively induces OVA-specific peripheral immunological tolerance, whether tested in normal BALB/c mice, OVA TCR Tg (DO11.10) mice, or in either BALB/c mice or Rag1 Ϫ/Ϫ mice transferred with OVA TCR Tg T cells. Consistent with our previous findings in other systems (17)(18)(19)(20)(21)(22), oral tolerance induction with Ag/CTB conjugate was superior to that induced with free Ag both in markedly increasing the efficacy of tolerization and in dramatically decreasing the effective amounts of Ag. The oral tolerance by i.g.…”
Section: Discussionsupporting
confidence: 91%
“…Oral administration of CT can in parallel with its adjuvant action prevent induction of oral tolerance to a coadministered Ag (17)(18)(19)33), although CT has also been reported (34) to promote the induction of T reg (Tr1 cells) in vitro. In this study, we found that coadministration of even very small amounts of CT together with the OVA/CTB conjugate effectively prevented the induction of CD25 ϩ CD4 ϩ suppressor T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrates that feeding minute amounts of insulin conjugated to CTB can significantly reduce the incidence of diabetes even when given as a single dose and that protection tends to be more durable when using five consecutive doses of conjugate. Taken together, these findings are in keeping with our previous observations (24,25) indicating that CTB can serve as a powerful transmucosal delivery system for inducing peripheral tolerance.…”
Section: Discussionsupporting
confidence: 80%
“…More recently, oral administration of a myelin autoantigen conjugated to CTB has been shown to protect animals against experimentally induced allergic encephalomyelitis, even when given after disease induction (25). We now report that feeding adult female NOD mice with small doses of heterologous insulin conjugated to CTB (CTB-insulin) prevents beta cell infiltration by diabetogenic T cells and protects animals against spontaneous autoimmune diabetes.…”
mentioning
confidence: 87%
“…16 Cytokines have been blocked using antibodies such as anti-TNF 17 and tolerance has been restored by feeding MBP 18 and cholera toxin conjugated to MBP. 19 For reviews on cytokines in inflammatory brain lesions see references 20 and 21. Intranasal administration of mutated MBP-specific peptides 22,23 and oral administration of PLP peptides 24 have been pursued in order to restore tolerance to myelin antigens.…”
Section: Immunotherapies Of Eaementioning
confidence: 99%